2012
DOI: 10.1002/nme.4358
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive atomistic‐to‐continuum modeling of propagating defects

Abstract: SUMMARY An adaptive atomistic‐to‐continuum method is presented for modeling the propagation of material defects. This method extends the bridging domain method to allow the atomic domain to dynamically conform to the evolving defect regions during a simulation, without introducing spurious oscillations and without requiring mesh refinement. The atomic domain expands as defects approach the bridging domain method coupling domain by fine graining nearby finite elements into equivalent atomistic subdomains. Addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…However, the concurrent modeling method reviewed in Section 5.3, borrowing ideas from the bridging scale method [344] and the bridging domain method [345], can exchange information and capture interaction between the fine scale and coarse scale in both directions. There is a tremendous amount of concurrent multiscale modeling methods developed in the recent ten years with rigorous mathematical foundations, but mostly for metals [344,[346][347][348][349][350] and carbon nanomaterials [345,[351][352][353][354]. These concurrent methods enable the information exchange between different length scales, capture their interactions and couple MD simulations with continuum simulations.…”
Section: From Atomistic To Macroscopic Scales and Backmentioning
confidence: 99%
“…However, the concurrent modeling method reviewed in Section 5.3, borrowing ideas from the bridging scale method [344] and the bridging domain method [345], can exchange information and capture interaction between the fine scale and coarse scale in both directions. There is a tremendous amount of concurrent multiscale modeling methods developed in the recent ten years with rigorous mathematical foundations, but mostly for metals [344,[346][347][348][349][350] and carbon nanomaterials [345,[351][352][353][354]. These concurrent methods enable the information exchange between different length scales, capture their interactions and couple MD simulations with continuum simulations.…”
Section: From Atomistic To Macroscopic Scales and Backmentioning
confidence: 99%
“…Promising approaches based on a concurrent coupling of a fine-scale model in the regions where fracture/dislocations occur with homogenized models elsewhere were presented. [64][65][66][67] Alternative methods propose to reduce the computational expense through algebraic model reduction. [68][69][70][71] Ultimately, these approaches aim at permitting to study structures of engineering relevance at an affordable computational cost.…”
Section: Mechanical Models Of Graphenementioning
confidence: 99%
“…Accordingly, we developed an adaptive scheme in which regions of atomistic simulation are dynamically adjusted to capture the moving crack front. Although this idea is similar to the work by Aubertin et al and Moseley et al , we demonstrated this implementation in the context of bridging scale method and space‐time FEM that builds capabilities of multiscaling in both space and time. Another significant implementation in the proposed method is the use of a coarse grained model based on virtual atom cluster representation introduced in that serves as a robust alternative to the conventional continuum modeling approach.…”
Section: Introductionmentioning
confidence: 58%